MOHAMMAD NATSIR DALAM DINAMIKA HUBUNGAN ANTARAGAMA DI INDONESIA - Mutohharun Jinan (Profetika: Jurnal Studi Islam, 2014)
This article discusses about the position of Mohammad Natsir in the dynamicof inter-religions relationship in Indonesia. Natsiris well-known as the public figure havinga great attention to the efforts for developing the life of peaceful religions in Indonesia.The efforts can be seen from his works and ideas. Natsir asks all people and leaders to usethe different religions as the potency to develop the peaceful life by having different religions.The religion Missionaries that break down the rules or government’s regulation becomesthe cause of the stress and inter-religions conflict. To create the peaceful life among thepeople with different religions, Natsir proposes the vivendimodus that consists of: thedifferent religious-people in Indonesia should live together harmonically, tolerance andappreciative each other, having priority on national development, avoiding the religionwar, and stressing on justice and religion diversity.Key Words: Mohammad Natsir; inter-religions relationship; religion diversity.Makalah ini membahas tentang posisi Mohammad Natsir dalam dinamikahubungan antaragama di Indonesia. Natsir dikenal sebagai tokoh yang memilikiperhatian besar dalam upaya membangun kehidupan keagamaan yang damai diIndonesia. Berbagai usahanya dapat dilihat dari pemikiran dan karya-karyanya. Natsirmengajak segenap pemimpin dan umat beragama memanfaatkan keragaman agamasebagai potensi untuk membangun kehidupan keagamaan yang damai. Misionarisagama-agama yang melanggar ketentuan atau peraturan pemerintah menjadi penyebabketegangan dan konflik antaragama. Untuk menciptakan kehidupan umat antaragamayang damai Natsir mengusulkan adanya modus vivendi yang meliputi: antara pemelukberagama di Indonesia supaya hidup berdampingan secara baik, saling menghargaidan toleransi, mengutamakan kepentingan pembangunan nasional, menghindariterjadinya perang agama, dan menekankan keadilan dalam keragaman beragama.Kata Kunci: Mohammad Natsir; hubungan agama-agama; Indonesia.